A FINITE ELEMENT METHOD FOR MODELING OF ELECTROMAGNETIC PROBLEMS - Vuong (Journal of Military Science and Technology, 2020)
Electromagnetic devices are present everywhere in our daily life. In particular, they extremely play an important role in the fields of the electrical system. Therefore, the modeling and analyzing the electromagetic problems become currently a matter of concern and topicality for researchers and designers of electrical devices. This paper introduces a finite element method to compute accurate distributions of leakage and fringing fluxes with air-gap variations, and eddy current losses of the magnetic circuits, that cannot generally be solved by a direct analytic method. The method is approached for the magnetic flux density formulation.